Two new species of Wedelia Jacq. (Asteraceae, Heliantheae) from Minas Gerais, Brazil - Bueno, Vinicius R.; Ferreira, Silvana C.; Nakajima, Jimi N. (Phytotaxa, 2020)
Two new species of Wedelia Jacq. are described and illustrated, and their morphological affinities with other species are discussed. Wedelia pauciflora is characterized by its solitary heads and a small number of flowers per head. Wedelia homogama is recognized by its shrubby habit, homogamous discoid heads, and purple corolla. These species were collected in Serra da Canastra National Park, São Roque de Minas, and in Rio Paranaíba; both areas are at Minas Gerais State, Brazil, occurring in “Cerrado” biome.